ZIP file of archived research website kinectic.net - Brown, Richard (Richard Brown, 2019)
This website documents a “Practise Based Research” PhD investigating Performative Interaction and Embodiment on an Augmented Stage. The research has been undertaken by Richard Brown , details of his previous work and background can be found here.